Impact of Remote Monitoring on Standardized Outcomes in Nephrology-Peritoneal Dialysis - Francisco Javier Centellas-Pérez; Agustín Ortega-Cerrato; Manel Vera; Ramón Jesús Devesa-Buch; Eduardo Muñoz-de-Bustillo; Mercedes Prats; Rafael Alonso-Valente; José Pedro Morais; Paula Jaro Cara-Espada; Claudia Yuste-Lozano; Marco Montomoli; Miguel González-Rico; et al. (Kidney International Reports)
Introduction: This study aimed to evaluate the association between the use of remote patient monitoring (RPM) in patients on automated peritoneal dialysis (APD) and the Standardized Outcomes in Nephrology in peritoneal dialysis (SONG-PD) clinical outcomes. Methods: A prospective and multicenter cohort study was conducted on patients with advanced chronic kidney disease on APD, recruited at 16 Spanish Hospitals, between June 1 and December 31, 2021. Patients were divided into 2 cohorts, namely patients on APD with RPM (APD-RPM) and patients on APD without RPM. The primary endpoints were the standardized outcomes of the SONG-PD clinical outcomes: PD-associated infection, cardiovascular disease (CVD), mortality rate, technique survival, and life participation (assessed as health-related quality of life [QoL]). Propensity score matching (PSM) was used to evaluate the association of RPM exposure with the clinical outcomes. Results: A total of 232 patients were included, 176 (75.9%) in the APD-RPM group and 56 (24.1%) in the APD-without-RPM group. The mean patient follow-up time was significantly longer in the APD-RPM group than in the APD-without-RPM group (10.4 ± 2.8 vs. 9.4 ± 3.1 months, respectively; P = 0.02). In the overall study sample, the APD-RPM group was associated with a lower mortality rate (hazard ratio [HR]: 0.08; 95% confidence interval [CI]: 0.01 to 0.69; P = 0.020) and greater technique survival rate (HR: 0.25; 95% CI: 0.11 to 0.59; P = 0.001). After PSM, APD-RPM continued to be associated with better technique survival (HR: 0.23; 95% CI: 0.06 to 0.83; P = 0.024). Conclusion: The use of RPM programs in patients on APD was associated with better survival of the technique and lower mortality rates. However, after PSM, only technique survival was significant.